1996
DOI: 10.1002/19960403nt2
|View full text |Cite
|
Sign up to set email alerts
|

Partial purification and characterization of an esterase from fusarium sporotrichioides

Abstract: Kinetics analysis of the growth of Fusarium sporotrichioides T-424 at 15 degrees C and 25 degrees C in liquid culture for 35 days revealed that production of deacetylated trichothecenes was associated with an increased activity in fungal esterases. High temperature (25 degrees C) favored enzyme production and enhanced esterase activity. Electrophoresis of crude extracts from the mycelia of F. sporotrichioides T-424 with carboxylesterase staining revealed that several esterases were produced by the fungus. Four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Thus, the sequential accumulation of 4,15-DAS, 15-MAS and SCIRP may reflect the inductive, and therefore successive, formation of esterases catalyzing the two steps from the esters to the parent alcohol SCIRP, with the appearance of substrate as the inducing event. This hypothesis is consistent with the observation of Park and Chu [29] that the production of deacetylated trichothecenes in F. sporotrichioides cultures on a liquid medium was associated with an increased total activity of fungal esterases. The successive formation of esterases apparently did not exclude the simultaneous presence of precursor and product during certain phases of fungal development (Figure 1, Figure 2).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Thus, the sequential accumulation of 4,15-DAS, 15-MAS and SCIRP may reflect the inductive, and therefore successive, formation of esterases catalyzing the two steps from the esters to the parent alcohol SCIRP, with the appearance of substrate as the inducing event. This hypothesis is consistent with the observation of Park and Chu [29] that the production of deacetylated trichothecenes in F. sporotrichioides cultures on a liquid medium was associated with an increased total activity of fungal esterases. The successive formation of esterases apparently did not exclude the simultaneous presence of precursor and product during certain phases of fungal development (Figure 1, Figure 2).…”
Section: Discussionsupporting
confidence: 93%
“…Different rates of formation due to genetic and environmental factors have been described. Thus, the production of DAS and MAS by strains of F. sporotrichioides in a liquid medium absorbed into vermiculate, investigated during an incubation of 20–30 days with five day intervals, varied considerably with the strain tested and also, in part, with the incubation temperature (25 or 15 °C) [29]. Overall, it can be concluded that, in grain samples collected at harvest, the analysis of SCIRP should be considered in addition to the analysis of 4,15-DAS and 15-MAS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the T‐2 and HT‐2 analysis, the disappearance of T‐2 and the extremely high HT‐2 recoveries (about 180%) led us to assume that T‐2 was converted into HT‐2 by enzymatic hydrolysis. Hydrolytic enzymes involved in selective deacetylation at the C3 and/or C4 positions of T‐2 toxin have been identified in animal organs,30, 31 as well as in crude extracts of Fusarium species 32, 33. Although trichothecene esterase activity has not so far been investigated in maize, carboxylesterase activities toward pesticide or xenobiotic esters have recently been identified in maize and sorghum 34.…”
Section: Discussionmentioning
confidence: 99%
“…sporotrichioides esterases were partially purified and characterized by Park and Chu (19,20). The esterase isozyme III, which had primarily C-3 esterase activity when assayed by conversion of 3-acetyl T-2 toxin to T-2 toxin, is a possible product of Tri8.…”
Section: Discussionmentioning
confidence: 99%